2017
DOI: 10.1038/pr.2017.48
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal resuscitation in global health settings: an examination of the past to prepare for the future

Abstract: As rates of childhood mortality decline, neonatal deaths account for nearly half of under-5 deaths worldwide. Intrapartum-related events (birth asphyxia) contribute to approximately one-quarter of neonatal deaths, many of which can be prevented by simple resuscitation and newborn care interventions. This paper reviews various lines of research that have influenced the global neonatal resuscitation landscape. A brief situational analysis of asphyxia-related newborn mortality in low-resource settings is linked t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…The need for neonatal resuscitation is most urgent in low-resource settings, where access to intrapartum obstetric care is poor and long-term impairments from intrapartum-related events represent a heavy burden [ 4 ]. While babies requiring advanced resuscitation may not survive without ongoing ventilation and neonatal intensive care, neonatal mortality from intrapartum-related events in low- and middle-resource settings can be reduced by 30% with basic training in neonatal resuscitation [ 5 ]. Expert consensus estimates a 10% reduction in intrapartum-related deaths with immediate newborn assessment and stimulation alone [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The need for neonatal resuscitation is most urgent in low-resource settings, where access to intrapartum obstetric care is poor and long-term impairments from intrapartum-related events represent a heavy burden [ 4 ]. While babies requiring advanced resuscitation may not survive without ongoing ventilation and neonatal intensive care, neonatal mortality from intrapartum-related events in low- and middle-resource settings can be reduced by 30% with basic training in neonatal resuscitation [ 5 ]. Expert consensus estimates a 10% reduction in intrapartum-related deaths with immediate newborn assessment and stimulation alone [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Retention of skills after initial neonatal resuscitation training in these countries has remained a challenge (5). The study by Rule et al (6) in this issue of Acta Paediatrica describes a rural Kenyan hospital health professional team's use of quality improvement (QI) techniques to decrease hypoxic ischaemic encephalopathy rates by 50% within six months of HBB training.…”
Section: Helping Babies Breathe Can Reduce Deaths With the Right Combmentioning
confidence: 99%
“… 14 It was then field tested in Bangladesh, India, Kenya, Pakistan, and Tanzania before being revised and released. 9 , 10 , 15 …”
Section: Introductionmentioning
confidence: 99%
“…These educational and neonatal care experts began to design a curriculum, develop implementation plans, and coordinate training efforts for an educational program to strengthen the knowledge and skills of birth attendants who care for mothers and babies in low-resource settings. 9 Since rollout of the program in 2010, HBB workshops have taken place in more than 80 countries—with the curriculum translated into 27 languages—and an estimated 500,000 providers trained. 9 , 16 Before and after studies of regional or facility-based HBB training in Africa and Asia have shown substantial decreases in very early neonatal mortality, stillbirth rates, and asphyxia-related morbidity and mortality when provider education was coupled with facilitated ongoing practice, quality improvement assessments, and local ownership of the program that integrated the content into routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%